Combustion Turbulence Flow in Trapped Vortex Combustor with Guide Vane and Blunt Body. (27th September 2020) - Zeng, Zhuoxiong; Guo, Kaifang; Gong, Xue
Abstract : Numerical calculation was conducted to obtain the optimum structure parameters of the trapped vortex combustor (TVC) with the guide vane and blunt body. The results show that the optimum structure parameters of the guide vane are a / H f = 0.5, b / L i = 0.2, and c / L = 0.1, and the optimum structure parameters of blunt body are S / L = 0.7, L 2 / L = 0.1, and L 1 / L i = 0.25 . Then, the influence of different inlet conditions on the combustion turbulence flow was studied. The results show that high inlet temperature and low inlet velocity can effectively reduce total pressure loss; the equivalence ratio has little effect on total pressure loss. The study of unsteady flow shows that double vortices undergo the process of preliminarily forming-breaking down-forming again-being stable gradually.